PHONOLOGICAL TRANSFORMATION IN ARABIC: A HISTORICAL STUDY OF I'LAL RULES BASED ON THE VIEWS OF AL-KHALIL BIN AHMAD AL-FARAHIDI - Rahmadini, Vira (Jurnal Al-Hibru, 2025)
This study discusses the phonological transformation in Arabic through a study of the rule of i'lâl - a process of phonetic change that occurs on the letters of illat (alif, wau, and ya') - in a historical perspective, by highlighting the contribution of Al-Khalil bin Ahmad al-Farahidi's thought. This study uses a qualitative approach with a literature study method, which aims to classify and analyze the types of i'lâl as described in the framework of shorof science (Arabic morphology). The results show that i'lâl has three main forms, namely ibdāl (replacement), ḥadhf (omission), and taskīn (harmonization), all of which are arranged to ease pronunciation and maintain harmony between sound and word structure. Al-Khalil bin Ahmad al-Farahidi is seen as the main figure in the early formulation of i'lâl theory, where his ideas not only provide a scientific foundation in morphological studies, but also show his accuracy in considering practical phonetic aspects in Arabic. Thus, this study emphasizes the importance of integration between phonology and morphology in understanding the dynamics of word formation, as well as the relevance of classical scientific heritage in the context of modern linguistics.